Long-term care (LTC) policy in Thailand on the homebound and bedridden elderly happiness - Savinee Suriyanrattakorn; Chia-Lin Chang (Elsevier, 2021)
The number of homebound and bedridden elderly has been increasing in Thailand, as the aging population rapidly grows and rates of chronic diseases increase. However, decreasing family size may reflect a decline in the ability of families to provide care. Society, as a result, enhances the need for long-term care (LTC) policy to provide home care and social support for the homebound and bedridden elderly. This paper examines how care-receipt satisfaction in LTC impacts the homebound and bedridden elderly's overall happiness, using a two-year panel of 279 individuals from the Thai Health Promotion Foundation dataset. We use the pooled two-stage least square (Pooled-2SLS) model and random effect two-stage least square (RE-2SLS) model to control the endogeneity problem. The empirical results show that care-receipt satisfaction on LTC service can generate a positive impact on the overall happiness of the homebound and bedridden elderly.